DESIGN OF AN ERGONOMIC TROLLEY FOR PLATE HANDLING TASK USING OVAKO WORKING POSTURE ANALYSIS AND ERGONOMIC FUNCTION DEPLOYMENT - Merry Siska; Muhamad Hifni Syahbana (Spektrum Industri, 2020)
The appointment of catering dishes at Dian Rasa Catering is currently still done manually by hand. Slouching work posture when lifting plates increases the risk of muscle and spinal injuries in workers. One way that can be done is to design ergonomic plate lifters. The design of an ergonomic trolley uses the Ergonomic Function Deployment (EFD) method. The attributes used are based on ergonomic aspects, which are effective, comfortable, safe, healthy, and efficient. Based on the attributes used, it can be seen the desires and needs of consumers for products which are then integrated with the technical characteristics of the tool. Obtained the results of the design of a catering plate lifter in the form of 3 plate racks with a radius of 21 cm that can accommodate 20 plates and trolleys with a height of 125 cm and the size of the trolley handle that can be adjusted according to the smallest body size (118 cm), on average (125 cm) ) and maximum (132 cm). The results of the experimental an ergonomic trolley help the employee to lift the plate, improve time efficiency and reduce the risk of muscle and bone injury to the catering employee. After the use of plate lifting tools catering harvest workers labor posture scores using the OWAS method dropped to 1.